Multimodal artistic metaphors: Research on a corpus of Sardinian art - Guerrieri, Alice; Ervas, Francesca; Gola, Elisabetta (Frontiers in Psychology, 2023)
The paper aims to define an artistic metaphor and highlight the multimodal properties of metaphors in artistic environments. Presenting a new categorisation for artistic metaphors intends to show that the visual, tactile and auditory components of the artworks can boost effective understanding of figurative meaning. Thus, the categories of 1) time, 2) space, 3) decontextualisation of stereotypes and 4) fusion of forms are applied to a corpus of artworks by important artists in the artistic and historical context of Sardinia. The multimodality of Sardinian artistic metaphors orients the observer towards original possibilities of learning and visual discovery for the knowledge of inheritance.